Pengaruh Kompensasi dan Promosi Jabatan terhadap Prestasi Kerja Melalui Motivasi sebagai Variabel Intervening Studi Kasus pada PT. Kurnia Alam Perista Kudus - Ane Anisa Maharani; Panca Winahyuningsih; Mia Ajeng Alifiana (Universitas Muhammadiyah Magelang, 2021)
This study aims to examine the analysis of compensation and promotion on job performance through motivation at PT. The Gift of the Holy Perista Nature. The sample of this research is 124 respondents with sampling using accidental sampling. This research test uses validity and reliability tests. Data analysis using AMOS SEM technique. Data collection was obtained from company records and documentation, interviews, and distributing questionnaires. The results of this study indicate that compensation has a positive and significant effect on motivation. Promotion has a positive and significant effect on motivation. Compensation has a positive and significant effect on work performance. Promotion has a negative and insignificant effect on work performance. Motivation has a positive and significant effect on work performance.